Validation of two algal names: Mallomonas camerunensis and Mallomonas cronbergiae ( Chrysophyceae , Stramenopiles ) - Jolanta Piątek (Plant and Fungal Systematics, 2021)
Two invalidly published chrysophyte species names, Mallomonas camerunensis and Mallomonas cronbergiae , are validated.